Analisa Fundamental Mikro Dan Fundamental Makro Terhadap Nilai Perusahaan Dengan Struktur Kepemilikan, Kinerja Keuangan, Struktur Modal Sebagai Variabel Intervening Pada Perusahaan Jasa Asuransi Yang Terdaftar Di Bursa Efek Indonesia - Rista; Hwihanus (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
This study aims to test and analyze the relationship between micro fundamental variability, macro fundamental to firm value, ownership structure, financial performance, and capital structure in Insurance Services Companies listed on the Indonesia Stock Exchange. Population search on 30 financial statements of Insurance Services Companies listed on the Indonesia Stock Exchange. This research method uses purposive sampling with a total sample of 10 companies with the years 2021-2023. The data analysis technique in this study uses Partial Least Square which consists of Inner Model, Outers Model and Weight Relation. The results showed that of the 13 hypotheses made, 3 hypotheses were accepted while 10 hypotheses were rejected. The test results show that 10 indicators have insignificant values.